Chapter Possibili scenari del modello TDDI - Infante, Pierpaolo (Strumenti per la didattica e la ricerca, 2022)
The physical removal from the school context due to the health emergency caused a sudden interruption, especially in an environment of exchange and relationship, creating important inconveniences on the 'well-being' of learners and teachers. Technology, which has always characterized human development, in its 'digital' dimension has triggered profound mutations, also leading to a profound reflection on teaching methods. Accepting with a critical sense and with adequate positivity the technological and digital evolutions could define a possible improvement of the educational, training and educational responses in a constantly changing social and economic ecosystem.